Răspunsuri

2014-09-28T22:35:45+03:00
1. x²+x<0 
il scriem pe x²+x sub forma x(x+1).
x(x+1)<0.  egalam ecuatia cu 0
x(x+1)=0
x=0
x+1=0⇒x=-1

facem tabel de semne

x        |-inf             -1           0            +inf
x        |---------------------------0++++++++
x+1    |----------------0++++++++++++++
x(x+1)|+++++++++0---------0++++++++

solutia finala:  x∈(-1;0)

2. x²≤9
x²-9≤0
(x-3)(x+3)≤0
x-3=0⇒x=3
x+3=0⇒x=-3

x               |-inf           -3           3             +inf
x-3            |-------------------------0+++++++++
x+3           |--------------0+++++++++++++++
(x-3)(x+3) |++++++++0----------0++++++++

solutia finala:  x∈[-3; 3]